The relationship between health literacy and marital satisfaction and quality of life of married women aged 30 to 40 in Mashhad - zahra Tavasoli; Fateme Nava (Mashhad University of Medical Sciences, 2017)
Background and objective: Marital satisfaction is to adapt between the person current status in marital relations to the situation he is expected and quality of life is defined differently by researchers and affected a variety of factors such as personal perceptions, emotions, culture, education and religious beliefs, the aim of this study was to investigate the relationship between health literacy and marital satisfaction and quality of life of married women 30 to 40 years in Mashhad. Methods: : The research method is Regression study in which 70 married women 30 to 40 years old in Mashhad with multi-stage cluster sampling method were selected to investigate the relationship between health literacy and marital satisfaction and quality of life. To collect data, Enrich marital satisfaction questionnaire, quality of Life short form of the World Health Organization, and Questionnaire of Functional Health Literacy Adults (test of functional health literacy in adults, TOFHLA) were used. Results: The results of descriptive analysis and selection married women were referred to clinics in Mashhad showed that there was a significant positive relationship between health literacy and marital satisfaction of married women (p